Resolving China's Corporate Debt Problem - Maliszewski, Wojciech (IMF Working Papers; Working Paper ;, 2016)
Corporate credit growth in China has been excessive in recent years. This credit boom is related to the large increase in investment after the Global Financial Crisis. Investment efficiency has fallen and the financial performance of corporates has deteriorated steadily, affecting asset quality in financial institutions. The corporate debt problem should be addressed urgently with a comprehensive strategy. Key elements should include identifying companies in financial difficulties, proactively recognizing losses in the financial system, burden sharing, corporate restructuring and governance reform, hardening budget constraints, and facilitating market entry. A proactive strategy would trade off short-term economic pain for larger longer-term gain.